Linking Empowering Leadership and Organizational Citizenship Behavior Toward Environment: The Role of Psychological Ownership and Future Time Perspective - Jiang, Meiqin (Front Psychol, 2019)
Organizations are confronted with increasing social responsibility to contribute to environmental sustainability. Employee organizational citizenship behavior toward the environment (OCBE) is considered essential to organizational environment performance. Drawing upon the theory of psychological ownership, the study investigated the effects of empowering leadership on employee OCBE by a sample of 374 employees in China. With the use of the bootstrapping technique in SPSS 25 to test our proposed moderated mediation model, results demonstrated a positive relationship between empowering leadership and OCBE through the mechanism of employee psychological ownership. Further, we found that the indirect effect is stronger when employees hold high rather than low future time perspectives. The theoretical implications for sustainability literature and practical implications for organizations striving for environmental sustainability are discussed.